1994
DOI: 10.1002/bmc.1130080105
|View full text |Cite
|
Sign up to set email alerts
|

Relations between blood pressure and plasma norepinephrine concentrations after administration of diltiazem to rats: HPLC‐peroxyoxalate chemiluminescence determination on an individual basis

Abstract: A calcium antagonist, diltiazem, was infused continuously into Sprague-Dawley rats through the left femoral vein at four different flow rates. The mean arterial blood pressure and concentrations of plasma norepinephrine (NE) were measured in each single rat (n = 5) and the correlations between them were studied. Blood (150 microL) was collected 13 times during the infusion. Plasma NE was determined by HPLC-ethylenediamine condensation reaction-peroxyoxalate chemiluminescence detection system (HPLC-ED-PO-CL). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
1
11
0
1
Order By: Relevance
“…In our present work as well as previous studies Higashidate et al, 1994;Imai et al, 1994) with SD Imai et al, 1994) and SH and WKY rats , we observed the quantitative correlation between an increase in plasma NE concentration and blood pressure reduction. This is presumably because the SNS released NE to maintain blood pressure up to normal levels responding to the blood pressure reduction caused by nicardipine.…”
Section: Relation Between Plasma L-arginine and Ne Concentrationsupporting
confidence: 72%
“…In our present work as well as previous studies Higashidate et al, 1994;Imai et al, 1994) with SD Imai et al, 1994) and SH and WKY rats , we observed the quantitative correlation between an increase in plasma NE concentration and blood pressure reduction. This is presumably because the SNS released NE to maintain blood pressure up to normal levels responding to the blood pressure reduction caused by nicardipine.…”
Section: Relation Between Plasma L-arginine and Ne Concentrationsupporting
confidence: 72%
“…For example, hypotensive responses caused by calcium antagonists in rats have been shown to correlate with the increases of plasma NE concentrations. Furthermore, we previously reported that the response was reduced in spontaneously hypertensive rats (SHR) as compared with that in normotensive Wistar-Kyoto (WKY) rats (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…3). 6 The more dull sympathetic nervous activity in the hypertensive rats (spontaneously hypertensive rats, SHR) as compared with that in the normotensive (Wistar Kyoto, WKY) rats was also clarified (Fig. 4).…”
Section: ·1 Blood Pressure Regulationmentioning
confidence: 90%
“…5 As described above (3·1), the trace analysis of blood catecholamines clarified the relation between the blood pressure and the sympathetic nervous system. 4,[5][6][7][8]47 …”
Section: ·3·2 Automatic Catecholamine Analyzermentioning
confidence: 99%